2020
DOI: 10.1108/ilt-04-2020-0143
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of tribo-mechanical properties of internal geometry structures of fused filament fabrication 3D-printed acrylonitrile butadiene styrene

Abstract: Purpose This study aims is to investigate the correlation between tribological and mechanical properties of the fused filament fabrication 3D-printed acrylonitrile butadiene styrene (ABS) pin with different internal geometries. Design/methodology/approach The tribological properties were determined by a dry sliding test with constant test parameters, while the hardness and modulus of elasticity were determined by microhardness and compression tests. Findings Although the internal geometry of the pin sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…The observations indicated that the graphene coating could minimize the coefficient of friction; however, the wear resistance of the coating was relatively poor. In their study, Norani et al 44 examined the relationship between the tribological and mechanical features of ABS polymer pins with diverse internal geometries fabricated using 3D printing technology. The tribological features were established through dry sliding tests with fixed factors, while hardness and modulus of elasticity were determined using microhardness and pressure tests.…”
Section: Introductionmentioning
confidence: 99%
“…The observations indicated that the graphene coating could minimize the coefficient of friction; however, the wear resistance of the coating was relatively poor. In their study, Norani et al 44 examined the relationship between the tribological and mechanical features of ABS polymer pins with diverse internal geometries fabricated using 3D printing technology. The tribological features were established through dry sliding tests with fixed factors, while hardness and modulus of elasticity were determined using microhardness and pressure tests.…”
Section: Introductionmentioning
confidence: 99%
“…1) ABS (Acrylonitrile Butadiene Styrene); 2) PLA (Polylactic Acid); 3) NYLON [15] . The process typically involves the use of a 3D printer to create a polymer substrate using an additive manufacturing technique such as fused deposition modelling (FDM) or stereolithography (SLA).…”
Section: Introductionmentioning
confidence: 99%
“…The process typically involves the use of a 3D printer to create a polymer substrate using an additive manufacturing technique such as fused deposition modelling (FDM) or stereolithography (SLA). A thin layer of metal foil, typically less than 100 micrometres thick, is then deposited onto the polymer sub-strate using a process such as thermal evaporation or sputtering [15] . Once the metal foil is deposited, the composite material is cured using a photopolymerization process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 3D FDM prints are mainly tested for their mechanical properties [16][17][18][19]. However, papers analyzing the tribological properties of FDM 3D prints are appearing more frequently [20][21][22][23][24][25]. The influence of additives on the tribological properties of 3D prints has also been described [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%